2015
DOI: 10.3402/gha.v8.26096
|View full text |Cite
|
Sign up to set email alerts
|

Health care in a homophobic climate: the SPEND model for providing sexual health services to men who have sex with men where their health and human rights are compromised

Abstract: We present a model for developing health services for men who have sex with men (MSM) in sub-Saharan Africa and other places where MSM are heavily stigmatized and marginalized. The processes of the SPEND model include Safe treatment for sexually transmissible infections (STIs) and HIV; Pharmacy sites for treatment of STIs in countries where pharmacies and drug stores are the source of medical advice and treatment; Education in sexual health issues for health professionals to reduce discrimination against MSM p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 31 publications
2
32
0
1
Order By: Relevance
“…Baral et al 28 demonstrated in a study from Nigeria that RDS could be used as a method of engaging MSM in antiretroviral therapy services. Models of engagement of MSM such as the SPEND model ((P) Pharmacies as treatment sources; (E) Educate health professionals; (N) Navigation for patients who must access the health system; and (D) Discrimination reduction), which integrates the RDS approach to increase MSM awareness of available services that are trusted, access such networks 29. While these communities are to a large extent ‘underground’ for protection against stigmatisation and victimisation, there is a potential to connect large MSM networks to trusted healthcare workers through RDS or other network-based approaches.…”
Section: Discussionmentioning
confidence: 99%
“…Baral et al 28 demonstrated in a study from Nigeria that RDS could be used as a method of engaging MSM in antiretroviral therapy services. Models of engagement of MSM such as the SPEND model ((P) Pharmacies as treatment sources; (E) Educate health professionals; (N) Navigation for patients who must access the health system; and (D) Discrimination reduction), which integrates the RDS approach to increase MSM awareness of available services that are trusted, access such networks 29. While these communities are to a large extent ‘underground’ for protection against stigmatisation and victimisation, there is a potential to connect large MSM networks to trusted healthcare workers through RDS or other network-based approaches.…”
Section: Discussionmentioning
confidence: 99%
“…Widely held negative views about gay men and men who have sex with men in Africa, even among health care workers and academics associated with HIV care and research [73], have restricted optimal support and care for African men who have sex with men, or even research on their behalf [74][75][76][77]. Criminalization reinforces those negative views, undermines care and research, and fuels the epidemic.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, in SSA, where gender-based ideas of homosexuality are prevalent, the assumption of a non-gay outward identity by MSM may be an adaptive strategy for protecting themselves against societal homophobic violence. This has been documented as a health-seeking strategy among South African and Tanzanian MSM [24,29,48]. Although the contentious concepts of "coming out" and "social visibility" have also been identified in other studies as protective factors leading to positive health outcomes in Western sample of MSM, they may be, however, counterproductive if adopted by MSM in homophobic cultural settings in SSA [44].…”
Section: Definition Evidence and Relevance Of Cultural Resilience Fmentioning
confidence: 99%
“…They are also socially marginalized, systematically excluded from HIV interventions and denied access to health services in a way that threatens the possibility of achieving an AIDS-free generation in Tanzania [48]. This poses a great challenge to HIV researchers and strongly indicates the urgent need for innovative HIVprevention approaches targeting not only Tanzanian MSM but all MSM in SSA.…”
Section: Cultural Resilience Among Msm In Ssamentioning
confidence: 99%
See 1 more Smart Citation